Migration and inequality in rental housing: Affordability stress in the Chinese cities. (February 2020) - Liu, Ran; Li, Tingzhu; Greene, Richard
Abstract: Housing affordability is a widely accepted notion used to assess the housing poverty problem in the Global North and South. China is experiencing an unprecedented urban revolution, with two-thirds of its 250 million migrants now being sheltered in the private rental housing sector of the receiving cities. The discriminatory hukou and an exclusive public housing system with appalling living conditions for migrant housing have been a huge challenge in contemporary China. In this paper, we aim to examine the state of housing affordability inequality in the current rental market for all of China and provide policy recommendations for a more accessible and equitable migrant housing provision system. On the basis of China's Migrant Dynamics Monitoring Survey (MDMS) conducted in 2011 and 2016, this paper analyzes the dynamic spatial inequalities of the rent affordability stress (rent-to-income ratio) among migrants from 2011 to 2016 across China's prefecture-level cities and above. We use CV, Gini and Theil indices to investigate the interregional, interprovincial and inter-prefectural inequalities of migrant rent stress, and then adopt spatial autocorrelation to examine the regional variance for these urban units. Our study reveals the convergence of rent stress inequality at different geographical scales and an increasingly apparent north-south divide in housing affordability inequality in the rental market accessible to the migrant workers of China. The agglomeration of the high rent-stress migrants in the "local buzz" in China is found, too, which is closely associated with policy and economic factors, as well as being embedded in the hierarchical structure of the Chinese urban administrative system and the contrasting urbanization paths of the north and south, and of the rustbelt and sunbelt. Highlights: Migrants' rent affordability stress is highly uneven in China. Rent stress is higher in the northeastern China and Beijing-Tianjin-Hebei. Inequalities tend to converge at different scales. High rent-stress migrants agglomerate in China's "local buzz". More inclusive housing policy should be designed.